Diagnóstico de la demanda eléctrica en el proceso de pelambre, curtido y terminado de pieles, para el rediseño del sistema de fuerza en la curtiembre San Isidro, parroquia Picaihua, provincia de Tungurahua - Masache Almeida, José Carlos (2017)
The objective of this research have to analyze the behavior of the electric demand in the San Isidro enterprise industry, through measurement and simulation tools, to get real data of the charge that make up and shape the electrical system, for this we carried out, censuses charge, the installation of an network analyzer in the electrical supply, in specific charges and on this way to propose solutions to get and to improve the performance of equipment, instruments and elements which are part of the electrical power system in this factory. Through the gotten data in eight days period with the network analyzer FLUKE 1735 we did the frequency histograms, by getting and average value of parameters as an active power, reactive power, apparent power, factor power, voltage levels and electricity currents in order to determine their respective daily behavior reactions....